Updating parameters of an information model for road construction flow in work development project - T. V. Bobrova (Вестник СибАДИ, 2023)
Introduction. The article reflects the main trends and problems in the development of information modelling technology in the Russian road industry. A set of mutually integrated domestic software products is presented that provide the formation and support of information models of roads in the life cycle process. It has been established that the transition from traditional simulation modelling of building flows to information modelling of flow systems requires a detailed analysis of the lower elements of the flow structure. Such elements in the system of an integrated road construction flow include linear specialized detachments.Models and methods. A single information model of an object as part of the construction organization project (COP) forms the overall strategy for managing the construction of the road. At the stage of the project for the production of works (PPW), it is necessary to take into account the technical and technological features of the contractor in the calendar plan. At the PPW level, it is necessary to create a new structure and define the parameters of this structure in such a way as to satisfy the specified restrictions established by the COP in terms of time and costs,  and also provide for certain reserves for insuring possible risks.  The aim of the study is to develop a methodology for information modelling of a specialized road flow as part of the PPW, taking into account the optimization and updating of its parameters in relation to the conditions of the contracting organization.Results. A modelling algorithm has been developed for creating an updated structure of a specialized linear flow in an integrated computer environment, which provides visualization of a construction site, control and operational management of work in a shared data environment. An example of the implementation of this method is considered when designing a specialized flow, first as part of a COP, with the subsequent updating of this model in the MS Project program when developing a PPW based on a typical flow chart.Conclusion. The use of information modelling creates wide opportunities for analyzing and monitoring the progress of work at the construction site of a linear flow, and also allows you to perform prompt automated restructuring of the loading of detachment vehicles when adjusting the amount of work at the work sites.